Incidence and Factors Associated with Incontinence Associated Dermatitis in Patient Ward Somdech Phra Debaratana Building Faculty of Medicine Ramathibodi Hospital : A Retrospective Matched-Paired Case Control Study Design - Utthiya, Pinyo; Koetsawat, Rungrat; Nuritanon, Jittima (Journal of The Royal Thai Army Nurses, 2023)
Incontinence Associated-Dermatitis (IAD) can cause discomfort, increase the treatment duration and costs. The objectives of this study were to determine the incidences and factors associated with IAD in a sample group of 64 patients based on historical data from January 1, 2021 to December 31, 2021. Content validity index (CVI) of data collection form developed by the researcher was .91, were reviewed retrospective paired study. The study adopted descriptive statistics, including percentage, mean and standard deviation. Statistics were analyzed using Chi-square test and binary logistic regression analysis to described the factors associated with IAD. The sample group was divided into several experimental groups, namely IAD case group (32 patients) and controlled group (32 patients). The patients’ genders and ages (±5 years) in each group were randomly matched and Barden score with 1:1 match. The study results indicated that IAD incidences in 2021 was 10.15% and the factors associated with IAD incidence, with statistically significance level of .05, consisted of excretory factors, such as watery bowel movements, health status factors, include fever, antibiotics, diuretics, sleeping pills/sedatives, nutritional deficiencies, length of hospital stay more than 15 days, O2 Saturation < 95% and oxygen requirement. The research results can be applied to create nursing practice guideline for IAD prevention and management.